2012
DOI: 10.1017/s0950268812001641
|View full text |Cite
|
Sign up to set email alerts
|

A population-based exposure assessment of risk factors associated with gastrointestinal pathogens: aCampylobacterstudy

Abstract: SUMMARYA questionnaire survey was undertaken to determine the exposure of a study population to campylobacteriosis source risk factors (environmental, water, food) and results were stratified by age, population density and deprivation. Data were gathered using an exposure assessment carried out by telephone in the Grampian region of Scotland. Univariate analysis showed that children aged 5-14 years, living in low population density (0-44 . 4 persons/km 2 ) and affluent areas had elevated exposure to environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Despite heterogeneity between sites, factors associated with reduced Campylobacter detection included exclusive breastfeeding, treatment of drinking water, access to an improved latrine, and recent use of antibiotics, particularly macrolides. These findings are consistent with other studies which have shown exclusive breastfeeding, water quality, and sanitation to be important determinants of Campylobacter infection [ 34 , 35 ]. These observations, along with the correlation between infection with Campylobacter and intestinal parasites, are suggestive of diffuse environmental exposure to Campylobacter .…”
Section: Discussionsupporting
confidence: 93%
“…Despite heterogeneity between sites, factors associated with reduced Campylobacter detection included exclusive breastfeeding, treatment of drinking water, access to an improved latrine, and recent use of antibiotics, particularly macrolides. These findings are consistent with other studies which have shown exclusive breastfeeding, water quality, and sanitation to be important determinants of Campylobacter infection [ 34 , 35 ]. These observations, along with the correlation between infection with Campylobacter and intestinal parasites, are suggestive of diffuse environmental exposure to Campylobacter .…”
Section: Discussionsupporting
confidence: 93%
“…The global disproportional burden of campylobacteriosis among young children is far from being understood ( 11 ). A recent study could not show increased exposure to known risk factors in young children compared with other age groups ( 12 ). Increased susceptibility because of immature immune systems, environmental contamination, cross-contamination in the kitchen, hand-to-mouth behavior, and overreporting have all been implicated.…”
Section: Discussionmentioning
confidence: 82%
“…The analyses focussed on Campylobacter jejuni infection as most cases are C. jejuni and other Campylobacter species- or subtypes have some specific risk factors [ 12 , 18 , 29 , 30 ]. The matched design allowed for control of age and season, two factors known to be confounders of the relationship between exposure and the disease [ 15 , 17 , 18 , 20 , 21 ]. The analysis was based on data collected from questionnaires for campylobacteriosis cases reported through an enhanced surveillance system and on data from a survey of healthy individuals from the same defined geographic region.…”
Section: Discussionmentioning
confidence: 99%